Study on Biochemical Parameters on Hydatid Cyst Layers (Laminated and Germinal) and Surrounding Host Tissues Isolated From Different Intermediate Hosts - MERZA, AHMAD S.; MERO, WIJDAN M.S . (Science Journal of University of Zakho, 2013)
This study included biochemical analysis of hydatid cysts (HCs) (laminated and germinal layers) and hosts tissues of sheep, goats and cattle during the period from Nov. 2010 to Oct. 2011. Furthermore, biochemical analysis of germinal layer of HCs surgically removed from human liver and lungs were also included in study. The chemical analysis involved the determination of cholesterol, triglyceride and nitrogenous compound. The germinal layer showed the highest content of cholesterol in HC of all hosts with the highest being in germinal layer of HCs in cattle liver (5.29 ± 0.65 mg/100g). Whereas, in host tissues, the highest level was observed in uninfected cattle liver tissues (35.71 ± 1.51mg/100g). The triglyceride in laminated layer of HC was higher than that in germinal layer in HCs of all hosts, with the highest being in the laminated layer of HCs in cattle lungs (11.85 ± 0.28 mg/100g). While in host tissues, the uninfected tissues showed the high level of triglyceride with the highest being in cattle lungs tissue (40.23 ± 0.97mg/100g).The laminated layer of HC in sheep lungs contained the highest level of urea and uric acid which were (4.45 ± 0.80 and 1.71 ± 0.68 mg/100g), respectively as compared with the cyst in other hosts. The uninfected sheep lung tissues, showed the highest level of urea (31.0 ± 0.88 mg/100g), while the highest level of uric acid was observed in sheep lung tissues which was in direct contact with the HCs (1.52 ± 0.35 mg/100g).Creatinine contents of laminated and germinal layers of HCs in sheep liver along with host tissue in direct contact with HCs were the highest among the studied hosts (0.12 ± 0.01, 0.17 ± 0.01 and 1.52 ± 0.17 mg/100g), respectively. The bilirubine content of laminated and germinal layers of HC in sheep lungs along with the host tissues which were in direct contact showed the highest level among all studied hosts (0.266 ± 0.02, 0.342 ± 0.03 and 0.63 ± 0.013 mg/100g), respectively.